Conceptualizing teacher professional identity in neoliberal times: Resistance, compliance and reform - Hall, David; McGinity, Ruth (Education Policy Analysis Archives, 2015)
This article examines the dramatic implications of the turn towards neo-liberal education policies for teachers’ professional identities. It begins with an analysis of some of the key features of this policy shift including marketization, metricization and managerialism and the accompanying elevation of performativity. This is followed by a discussion of the implications of this turn for teachers in which a new professionalism of increasing regulation and restrictions upon practice in a policy environment dominated by neo-liberalism act to restrict and confine professional identity formation and development. Drawing upon data collected within English schools the article explores how teachers have responded to this new policy environment in ways that are sensitive to how neo-liberal policy has been re-contextualized and re-translated in different educational settings. This reveals both the power of this New Right inspired permanent revolution of educational change in English schools and the complexities of how it has been variously embraced, accommodated and resisted by teachers. The article concludes with a discussion that explores the meaning of resistance in the context of what are identified as restricted teacher professional identities where affordances for professional practices lying outside of neo-liberal subjectivities have been dramatically reduced.